The Sustainable Development of Competitive Enterprises through the Implementation of Innovative Development Strategy - Malysheva, Tatiana V.; Shinkevich, Alexey I.; Kharisova, Guzyal M.; Nuretdinova, Yuliya V.; Khasyanov, Oleg R.; Nuretdinov, Ildar G.; Zaitseva, Natalia A.; Kudryavtseva, Svetlana S. (International Journal of Economics and Financial Issues, 2016)
The purpose of this article is to develop methodological approaches to the production effectiveness's evaluating and products competitiveness's level estimation to identify risk groups according to the products and producers, to propose targeted measures manufacturers' support, to activate innovative development and minimize potential social impacts. The leading method to study this problem is the method of constructing the matrix of the producers' efficiency and the commodities' competitiveness which allows implement a differentiated approach to the strategies' development of production's innovative development and social risks' minimization. The article proposes a methodological approach to the products competitiveness's level assessment based on the efficiency of production and external conditional factors and identifies the respective groups of competitive and non-competitive commodities and producers, as well as it defines the resource and innovation potential, with further strategy development. The study materials can be used in the management of manufacturing development, both at the level of the industrial enterprises' services and government agencies, to assess the level of products' competitiveness, to create strategies of innovation development, to develop targeted actions for the exports' development. Keywords: commodities' competitiveness, production efficiency, export potential, innovation development JEL Classifications: O31, O34, Q01